Saint Thecla, Saint George and Saint Barbara: The monarchs of Aragon to the search for relics in the Orient (14th and 15th centuries) - BAYDAL SALA, Vicent (Anaquel de Estudios Árabes, 2010)
Virtually since its inception Christianism was characterized by veneration of relics of biblical figures, martyrs and saints. Afterwards, with the emergence of feudal monarchies and the expansion of European society from the eleventh century, the Oriental relics became one of the most coveted objects by western kings both for its economic value as for its symbolic function. In the case of the Crown of Aragon, the monarchy carried out an active policy of relics’ acquisition from the early fourteenth century to the beginning of the fifteenth one, in which highlighted three particular cases: the arm of Saint Thecla, preserved in Armenia the head of Saint George, in Greek lands, and the body of Saint Barbara, in Cairo. Overall, although the Catalan-Aragonese monarchy only got the first relic, the repeated attempts to get the other two show that traffic of sacred remains was one of the most intense points of military, diplomatic, commercial and identity contact between the West and Eastern societies during the late medieval period.
Keywords: Armenia; Crown of Aragon; Cult of saints; Egypt; 14th and 15th centuries; Greece; Relics